Development of a chitin/graphene oxide hybrid composite for the removal of pollutant dyes: Adsorption and desorption study - González, Joaquín Antonio (2015)
This work presents the synthesis of chitin (Chi) and chitin/graphene oxide (Chi:nGO) hybrid gels in mild conditions and their use as biosorbents in solid-liquid batch systems. The graphene oxide nanosheets, obtained from natural graphite through Hummers method, were characterized using FT-IR, ESR and pHpzc determination as a qualitative approach of the degree of exfoliation and oxidation. Two kinds of widely used dyes were tested: Remazol Black (RB) as an acid dye model and Neutral Red (NR) as a basic dye model. Adsorption assays results were analyzed using two and three parameters isotherm models. The maximum adsorption capacity (qm) for RB and NR were 9.3×10-2mmol/g and 57×10-2mmol/g being the first one reached by Chi and the second by the hybrid. Furthermore, the adsorption behavior over the time was evaluated through pseudo-first, pseudo-second, Elovich and Modified Freundlich models being the first one which described better all the cases except the adsorption of Remazol Black on chitin gel which follows an Elovich tendency. According to the pseudo-first order model, the uptake rates (k1) were between 1.1×10-2min-1 and 1.4×10-2min-1, but for the Chi:nGO-NR system it was 1.7×10-3min-1. The adsorption was observed to be dependent on both the solution pH and the Chi:nGO proportion. Finally, both dyes can be desorbed from both kinds of materials up to 60% of the sorbed amount by increasing the solution pH above 8. This would imply the capability of reutilization of the material with minor sorption capacity.